Pengukuran Tingkat Kelembapan Tanah Dan Suhu Berbasis Arduino Uno pada Kelompok Tani Karya Maju II (Dua) - Armanto Armanto; Andri Anto Tri Susilo; Harma Oktavia Lingga Wijaya; Wisdalia Maya Sari (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Electronic technology has recently developed rapidly, almost all aspects of daily human life have been covered by equipment with electronic technology systems, both using analog and digital control systems. Measurement is very important in science, especially in engineering. Measurement plays an important role in helping human work. As a country with vast natural resources, agriculture has enormous potential as state revenue. In addition, the agricultural sector is one of the most important sectors that increase the economic growth of the Indonesian people. One of the most important factors in agriculture is the quality of agricultural land. The better the agricultural land, the agricultural output will also increase. Factors that affect the quality of agricultural land are soil moisture and temperature. The life of biological elements contained in the soil including hosts, pathogens, and other microorganisms which vary greatly is influenced by soil moisture factors. condition of agricultural land in the area of Air Satan village. farmers in the air satan village have difficulty monitoring soil fertility in agricultural areas in the air satan village area, therefore the author wants to develop a tool that functions to measure the level of soil moisture with the measurement results displayed using a 16x2 LC which can be directly seen in order to make it easier for farmers or farmer groups in monitoring soil moisture and temperature in the agricultural area of Airsatan Village.